Apparel merchandising process of Poeticgem International Ltd. (A Concern of PDS Multinational Group) - Islam, Md. Ridwanul (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.